Enhancing Statistical Literacy Using ChatGPT-Assisted E-Worksheets: A Differentiated Learning Approach Based on Adversity Quotient - Fertikawati, Ratna; Gunawan, Gunawan; Ong, Eng Tek (Jurnal Pendidikan MIPA, 2025)
Enhancing Statistical Literacy Using ChatGPT-Assisted E-Worksheets: A Differentiated Learning Approach Based on Adversity Quotient. Objective: The research aims to develop an innovative, ChatGPT-assisted e-worksheet in differentiated learning that meets valid, practical, and effective criteria to enhance students' statistical literacy skills. Methods: The study involved 98 grade VII junior high school students. The research and development method adopted the 4D design, consisting of define, design, develop, and disseminate stages. Data were collected by interviews, observations, questionnaires, and statistical literacy tests. Data analysis employed descriptive statistics and inferential tests, including mean values, normality tests, homogeneity tests, and ANCOVA tests. The learning design includes experimental and control classes. Both classes were taken using a simple random sampling technique. Findings: The results indicated that the ChatGPT-assisted e-worksheet met the standards of validity and practicality. The validity experts obtained a validity score of 94.27%, which falls within the valid category, and the practicality test achieved a score of 84.21%, which is categorized as practical. In addition, the e-worksheet product ChatGPT is effective in improving statistical literacy skills. The results of the statistical literacy ability test met the normality and homogeneity criteria, and the ANCOVA test showed a significance value of 0.000 < 0.05, indicating a statistically significant effect. The results confirm that the experimental class achieved higher statistical literacy scores than the control class. Conclusion: The e-worksheet product effectively improved learning achievement, particularly in literacy and statistics skills. The e-worksheet was developed according to the learning needs of students, specifically those with the adversity quotient (AQ) type. Each type of AQ climber, camper, and quitter has a different worksheet, making it easier for students to learn. The AQ differentiated approach resulted in a significant increase in literacy scores. ChatGPT-assisted e-worksheet could be applied in statistical learning as an educational technology innovation that enhances student achievement. The learning atmosphere becomes more fun and meaningful for students.    Keywords: chatgpt, differentiated learning, e-worksheet, statistical literacy skills.